Nesting ecology of the olive Ridley sea turtle (Lepidochelys olivácea)(Cheloniidae)at El Valle beach, northern Pacific, Colombia. (2014)
ABSTRACT : The olive ridley (Lepidochelys olivacea) is the most common sea turtle to nest in Colombia. El Valle beach is considered the most important nesting beach for this species in South America. Intensive direct capture of nesting females and egg poaching for consumption and local commercial purposes has been a common practice for years. We conducted an analysis of the nesting ecology of the olive ridley on El Valle beach in the northern Pacific of Colombia in 2008. A total of 164 clutches were transferred to an artificial hatchery for protection. The peak of nesting occurred from the second half of August until the end of September, accounting for 64.6 % of all nests. Along the beach, the section most frequently used was Section 3, with 26 % of the nests. The nests were laid mainly in zone 3.69 %. We encountered 55 nesting females and marked 46 of them. Mean CCL was 64.9 ± 2.4 cm and mean CCW was 68.6 ± 2.6 cm. Females laid on average of 87.3 ± 14.2 eggs per clutch. We recorded two nesting events per female, with a mean inter-nesting period of 18.8 ± 4.2 days. The reproductive output for the season was 181.5 ± 34.8 eggs / female. Mean hatching success was 81.1 ± 12.1 % and mean emergence success was 77.6 ± 12.7 %. The incubation period was 65 ± 4.7 days. Our study is a valuable contribution to knowledge of the reproductive ecology of the olive ridley population regionally and globally.